The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/batt.202100379
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur/Nitrogen Co‐Doped In‐Plane Porous Carbon Nanosheets as Superior Anode of Potassium‐Ion Batteries

Abstract: Carbonaceous materials are regarded as prospective anode candidates of potassium‐ion batteries. However, the rate capability and cycling stability of classic carbon materials are still far from satisfactory. Herein, we exploit a facile and low‐cost strategy to enable the precise synthesis of sulfur/nitrogen co‐doped in‐plane porous carbon nanosheets with fishnet‐shaped microstructure (SN‐CNSs). The well‐designed in‐plane porous structure and the interconnected carbon flake network can accelerate the diffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…The capacitive contribution rates were determined to be 46.8, 50.4, 61.1, 68.9, and 70.6% at scan rates of 0.1, 0.2, 0.4, 0.6, and 1 mV s –1 , respectively (Figure f). The high capacitive contribution rate promotes long-term stability and rate performance …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacitive contribution rates were determined to be 46.8, 50.4, 61.1, 68.9, and 70.6% at scan rates of 0.1, 0.2, 0.4, 0.6, and 1 mV s –1 , respectively (Figure f). The high capacitive contribution rate promotes long-term stability and rate performance …”
Section: Resultsmentioning
confidence: 99%
“…The high capacitive contribution rate promotes long-term stability and rate performance. 53 The electrochemical performances of the RGE and RGE/RP electrodes were compared (Figure 5a). In terms of cycling performance, the RGE electrode demonstrated a stable cycling performance at 0.2 A g −1 with minimal capacity decrease, which is comparable to that of commercial graphite (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…From DFT calculations, Li et al found that sulfur/nitrogen co-doping in carbon nanosheets increases their attraction for potassium. 131 According to Ling et al, the larger cations are inserted at higher voltages into iron hexacyanoferrate, and the migration of the larger cations is slower. 176 The ionic radius influences the preferred insertion site.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…130 The sulfur/nitrogen co-doping of carbon nanosheets can accelerate the diffusion of potassium ions, alleviate volume expansion and increase the capacity up to 248 mA h g −1 after 4500 cycles in potassium-ion batteries. 131 It seems that N and S are not bonded together, and the synergistic effect occurs through N–C–S bonds in the hexagonal rings of the graphene sheets. The sodium cell based on S and P co-doped carbon exhibits a remarkable cycling life (3000 cycles), and it was attributed to the adsorption of sodium on the surface of carbon particles.…”
Section: Effects Of Multianions On Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation